A Multi‐Analytical Approach to the Study of the Mural Paintings in the Presbytery of Santa Maria Antiqua Al Foro Romano in Rome. (28th March 2017) - Amato, S. R.; Bersani, D.; Lottici, P. P.; Pogliani, P.; Pelosi, C.
Abstract : This paper presents the results of analyses carried out on three decorative phases of the presbytery of the church of Santa Maria Antiqua al Foro Romano in Rome: the fourth‐centuryad mosaics setting bed; the Adoration of the Cross, dated to the papacy of John VII (ad 705–7); and the paintings in the apse of the Pope Paul I (ad 757–68) phase. The research allowed the characterization of the painting techniques, pigments, organic compounds and degradation products by means of a video microscope, optical microscopy, and μ‐Raman and FT–IR spectroscopy, contributing to a better understanding of the changes in the techniques and materials used throughout the centuries in one of the most relevant medieval Christian monuments in Western Europe.